A STUDY ON ISOLATION OF CHEMICAL CONSTITUENTS FROM SOPHORA FLAVESCENS AIT. AND THEIR ANTI-GLIOMA EFFECTS - Zheng, Kebin; Li, Chunhui; Shan, Xiaosong; Liu, Haipeng; fan, Wufang; Wang, Zhenshan (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: Sophora flavescens Ait. is a traditional Chinese medicine with a long history in China. It is mainly used in the treatment of heat dysentery and similar ailments in the clinical. The objective of this paper was to isolate, purify and identify alkaloids from Sophora flavescens Ait. and to explore their inhibitory effects on C6 glioma cells. Materials and Methods: Column chromatography, extraction and NMR spectroscopy were used to structurally identify the isolated compounds. MTT assay and flow cytometry were used to detect the inhibitory effect of matrine on C6 cells. Results: Three compounds were isolated from Sophora flavescens Ait., namely matrine, oxymatrine and lupeol. Different concentrations of matrine solution all had inhibitory effects on growth of C6 cell lines, which showed apparent dose-effect relationship. Compared with the control group, proportion of G0/G1 phase cells increased in each matrine concentration group to a maximum of 79.8%; proportion of S phase cells reduced, and proportion of G2/M phase cells declined slightly to a minimum of 6.3%, suggesting that after the action of matrine proliferation of C6 cells was significantly inhibited and the cells were arrested in the G1 phase. Conclusion: We concluded that Sophora flavescens Ait. has an inhibitory effect on C6 cell proliferation.